KINETICS OF ZINC AND ARSENATE CO-SORPTION AT THE GOETHITE-WATER INTERFACE - Gräfe M.; Sparks D.L. (My University, 2005)
Little or no information is available in the literature about reaction processes of co-sorbing metals and arsenate [As(V)] on variable-charged surfaces or factors influencing these reactions. Arsenic and metal contamination are, however, a common co-occurrence in many contaminated environments. In this study, we investigated the co-sorption kinetics of 250 μM As(V) and zinc [Zn(II)] in 10, 100, and 1000 mg goethite L−1 0.01 M NaCl solution at pH 7, collected complementary As and Zn K-edge extended X-ray absorption fine structure (EXAFS) data after various aging times, and performed a replenishment desorption/dissolution study at pH 4 and 5.5 after 6 months of aging time. Arsenate and Zn(II) formed adamite-like and koritnigite-like precipitates on goethite in 100- and 10-ppm goethite suspensions, respectively, whereas in 1000-ppm goethite suspensions, As(V) formed mostly double-corner sharing complexes and Zn(II) formed a solid solution on goethite according to EXAFS spectroscopic analyses. In all goethite suspension densities, surface adsorption reactions were part of the initial reaction processes. In 10- and 100-ppm goethite suspensions, a heterogeneous nucleation reaction occurred in which adamite-like precipitates began to form 48 h earlier than koritnigite-like surface precipitates. Arsenate and Zn(II) uptake from solution decreased after 4 weeks. Replenishment desorption studies showed that the precipitates and surface adsorbed complexes on goethite were susceptible to proton-promoted dissolution resulting in many cases in more than 80% loss of Zn(II) and ∼ 60% to 70% loss of arsenate. The molar Zn:As dissolution ratio was dependent on the structure of the precipitate and was cyclic for the adamite and koritnigite-like surface precipitates, reflecting the concentric and plane-layered structures of adamite and koritnigite, respectively.